Effect of aging on cerebral tissue oxygenation in relation to reflex syncope. (24th May 2021) - Kharraziha, I; Torabi, P; Johansson, M; Sutton, R; Fedorowski, A; Hamrefors, V
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Swedish Heart and Lung Foundation, The Swedish Heart and Lung Association, ALF funds, Skåne University Hospital Funds, The Crafoord Foundation. Background: There is an increased susceptibility to syncope with aging attributed to age-related physiological impairments. Cerebral oximetry non-invasively measures cerebral tissue oxygenation (SctO2) and has been shown to be valuable in syncope evaluation. SctO2 has been found to decrease with aging but it is unknown whether the decrease in SctO2 is related to increased susceptibility to syncope during orthostatic provocation. By measuring SctO2 during head up tilt test (HUT) we can study age-related differences in SctO2 and their impact on developing reflex syncope. Purpose: To investigate the effect of age on the cerebral tissue oxygenation threshold for syncope and presyncope among patients with vasovagal syncope. Methods: Non-invasive haemodynamic monitoring and near-infrared spectroscopy (NIRS) were applied during head-up tilt (HUT) in 139 vasovagal syncope patients (mean [SD] 45[17] years, 60% female), and 82 control patients with a normal response to HUT (45[18] years, 61% female). Group differences in SctO2 and systolic blood pressure (SBP) during HUT in supine position, after 3 and 10 min of HUT, 30 seconds prior to syncope ("presyncopal phase") and during syncope in different age groups (<30, 30-60 and  >60 years) were compared using one-way ANOVA and Tukey"s multiple comparison test. Associations between age and SctO2 were studied using linear regression models adjusted for sex and concurrent SBP. Results: Lower SctO2 in supine position was associated with increasing age among controls (B=-0.085, p = 0.010) but not among VVS patients (B=-0.036, p = 0.114). No age-related differences in SctO2 were found after 3 and 10 minutes of HUT and during syncope.  Mean SctO2 (%) during the presyncopal phase decreased over the advancing age groups (<30: 66.9 ± 6.2, 30-60: 64.5 ± 6.1, >60: 62.2 ± 5.8; p = 0.009 for inter-group comparison). In contrast, mean SBP during the presyncopal phase did not differ by age groups (<30: 85.6 ± 21.8, 30-60: 77.6 ± 19.7, >60: 77.6 ± 20.8 mmHg, p = 0.133). Age was associated with lower SctO2 during the presyncopal phase after adjusting for sex and SBP (B = 0.096, p = 0.001). Conclusion: Older VVS patients have lower cerebral tissue oxygenation in the presyncopal phase compared with younger patients independently of systolic blood pressure. These results suggest either that with imminent reflex syncope cerebral tissue oxygenation diminishes more with advancing age or that cerebral deoxygenation is better tolerated by older reflex syncope patients.